Improving the quality of discharge summaries for elective surgical procedures at North Bristol NHS Trust. Issue 1 (11th February 2015) - Ladds, Emma; Betteridge, Frederica; Yamamoto, Sarah; Gupta-Jessop, Thomas
Abstract: Following elective surgical procedures, hospital discharge summaries are essential in the handover to primary care. The information provided varies between institutions and is highly user-dependent. Various interventions have focused on improving information transfer to patients and primary care physicians including the development of electronic templates, electronic transmission to primary care, and training initiatives for junior doctors. An evaluation of the urological patient's journey at Southmead Hospital revealed a need for improved discharge summary advice. Urology specialists developed "gold standard" templates for elective urological procedures. Following a new rotation of junior doctors, discharge summaries were audited for one week. The templates were then made available on the urology ward, a teaching session was employed to encourage compliance, and the hospital electronic discharge summary template was edited. Following each intervention, summaries for one week of urology procedures were audited to assess the quality of advice provided to patients. At baseline, 18% of discharge summaries contained sufficient patient advice, this reduced to 10% after templates were made available on the wards, increasing to 45% following the education session and 84% once the electronic discharge summary proforma was edited. We conclude that discharge summaries are an effective time point for intervening to provide patients with specific post-operative information and this may be optimised for different elective procedures via the introduction of electronically-distributed standardised templates.